Optimization of Batch Production of Bifidobacterium Pseudocatenulatum G4 in A Milk-Based Medium - Wong, Stephenie Yoke Wei (2006)
This study was undertaken to optimize the production of probiotic in a milk-based medium and to establish process parameters for the batch cultivation of Bifidobacterium pseudocatenulatum G4. The locally isolated strain exhibited high tolerance to pH 1.0-3.0 and fulfilled other probiotic criteria. Identification of the organism was done using polymerase chain reaction (PCR) based method. A defined band at 1.35 kb and 289 bp were produced using genus-specific and species-specific 16S rRNA primers, respectively. An initial screening of bacteria were done using 23 full factorial design in order to identify the effect of medium components consisting of skim milk, yeast extract and glucose towards biomass production. Results showed that yeast extract had a significant positive effect on viable cell count whereas glucose resulted in a negative effect, which was then eliminated from the study. Response surface methodology (RSM) was then applied to optimize the use of skim milk and yeast extract. A quadratic model was derived using a face-centered central composite design to represent cell mass as a function of the two variables. The optimized medium composition of 2.8% (w/v) skim milk and 2.2% (w/v) yeast extract gave the maximum biomass concentration of 1.3 x 109 cfu mL-1, which was 3 log unit higher compared to the commonly used 10.0% (w/v) skim milk (6.3 x 105 cfu mL-1). The application of RSM resulted in an improvement in biomass production in a more cost-effective medium, where the skim milk composition was reduced by 71.8%. Further improvement on the biomass production was carried out in a 2-L stirred tank bioreactor. The highest viable cell count was obtained at pH 6.5, with 0.56 ms-1 impeller tip speed. Scaling-up fermentation to a 10-L stirred tank bioreactor based on constant impeller tip speed (0.56 ms-1) successfully yielded reproducible fermentation kinetic values. The results were similar to the smaller-scale reactor. Under this condition, the following were obtained: maximum biomass concentration, Xmax (1.4 x 109 cfu mL-1), maximum specific growth rate, μmax (0.48 h-1), biomass productivity, Px (7.70 x 107 cfu mL-1 h-1), and biomass yield, Yx/s (9.46 x 1010 cfu g lactose-1). The survival of B. pseudocatenulatum G4 during freeze-drying and spray-drying processes was also evaluated. During freeze-drying, the strain exhibited high percentage survival (71.7 - 82.1%) when different combinations of skim milk and sugar solutions (glucose, sucrose and lactose) were used as cryoprotectants. The viable cell counts of 2.1 x 109 cfu g-1 to 3.1 x 109 cfu g-1 were obtained after the lyophilization process. Since the addition of sugar did not result in higher percentage survival, 10.0% (w/v) skim milk was suggested as a suitable cryoprotectant. On the other hand, the strain experienced over 99.0% loss in viability after spray-drying regardless of the spray-drier air outlet temperature and use of heat-adaptation treatments.